2014
DOI: 10.1039/c4qo00109e
|View full text |Cite
|
Sign up to set email alerts
|

Polythiophene synthesis via halogen dance

Abstract: Polymerization of thiophene with a Ni(ii) catalyst through halogen dance leads to a new class of polythiophenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Scheme 1 Preparation of thiophene monomer 4a bearing benzenesulfonate group at the 3position Polymerization of the thus obtained chlorothiophenes 4a was carried out by the reaction with a bulky magnesium amide TMPMgCl•LiCl (2,2,6,6-teteramethylpiperidine-1-yl chloromagnesium: Knochel−Hauser base) 44 to undergo deprotonative metallation. [26][27][28][29][30][31][32][33][34][35] The addition of nickel catalyst 6 5 to the thus formed thiophene−magnesium species followed. Smooth polymerization took place at room temperature as shown in Scheme 2 to afford the corresponding polythiophene 6a in 66% yield as deep orange solid as shown in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scheme 1 Preparation of thiophene monomer 4a bearing benzenesulfonate group at the 3position Polymerization of the thus obtained chlorothiophenes 4a was carried out by the reaction with a bulky magnesium amide TMPMgCl•LiCl (2,2,6,6-teteramethylpiperidine-1-yl chloromagnesium: Knochel−Hauser base) 44 to undergo deprotonative metallation. [26][27][28][29][30][31][32][33][34][35] The addition of nickel catalyst 6 5 to the thus formed thiophene−magnesium species followed. Smooth polymerization took place at room temperature as shown in Scheme 2 to afford the corresponding polythiophene 6a in 66% yield as deep orange solid as shown in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Scheme 4, the prepared monomer 4a was employed for statistical copolymerization with 2-chloro-3-hexylthiophene ( 11) with a nickel(II) catalyst. [26][27][28][29][30][31][32][33] Copolymerization of 4a and 11 was carried out using 1-20 mol % of 4a. A mixture of 4a and 11…”
Section: Synthesis and Characterization Of A Polyacetylene Derivativementioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown that 2,5‐dibromothiophene 3 similarly afforded lithiated thiophene 2 (M=Li), and the thus formed 2 polymerized by the addition of nickel catalyst 19 , while the use of LDA (LiN i Pr 2 ) toward 3 induced deprotonation at the β‐position of the thiophene ring and halogen dance followed to afford α‐lithiated thiophene (Scheme ). The addition of nickel catalyst underwent polymerization to afford a new class of polythiophene bearing a carbon–bromine bond (halogen dance polymerization) …”
Section: Deprotonative Preparation Of the Monomer Species In Ht‐regiomentioning
confidence: 99%
“…17 Treatment of the polymer in THF under reflux for 1 day formed the debrominated product as shown in Scheme 5(a). Reductive transformation of (3T-Br) n proceeded with tBuMgCl as a reducing agent in the presence of NiCl 2 dppf as a catalyst.…”
mentioning
confidence: 99%